Enhanced recovery after minimally invasive heart valve surgery: Early and midterm outcomes. (1st January 2023) - Berretta, Paolo; De Angelis, Veronica; Alfonsi, Jacopo; Pierri, Michele D.; Malvindi, Pietro Giorgio; Zahedi, Hossein M.; Munch, Christopher; Di Eusanio, Marco
Abstract: Background: Although the use of protocols for "enhanced recovery after surgery" (ERAS) have been associated with improved results in different surgical specialties, only a few data are available for ERAS in cardiac surgery. This study aimed to compare 30-day outcomes of patients undergoing ultra-fast-track minimally invasive valve surgery (UFT-MIVS) versus conventional MIVS (c-MIVS). Methods: The key features of UFT-MIVS approach involves: 1) less invasive valve surgery techniques, 2) normothermic cardiopulmonary bypass management, 3) UFT-anesthesia with table extubation, 4) immediate rehabilitation therapy and patient-family contact. Five-hundred and seventy-six consecutive patients who underwent aortic or mitral MIVS were analyzed (2016–2020). Treatment selection bias (UFT-MIVS vs. c-MIVS) was addressed by the use of propensity score (PS) matching. After PS-matching 2 well-balanced groups of 152 patients each were created. Results: In the matched cohort, the overall 30-day mortality and stroke rates were 0.3% and 0.7%, respectively, with no difference between groups. UFT-MIVS resulted in lower rates of respiratory insufficiency and agitation/delirium compared with c-MIVS. Patients receiving UFT-MIVS were associated with significantly shorter intensive care unit length of stay and hospital stay. Conclusions: Our study confirms that MIVS is associated with excellent results in terms of early mortality and major postoperative complications rates. The implementation of UFT-MIVS protocol showed to be safe and was associated with improved clinical outcomes in regard to respiratory insufficiency, delirium and lengths of stay. Graphical abstract: Unlabelled Image Highlights: The ERAS program in cardiac surgery was built within a multidisciplinary team. The key features of our ERAS protocol involves UFT anesthesia with table extubation, and immediate rehabilitation therapy. ERAS protocols can be implemented safely in minimally invasive valve surgery. Ultra fast track management showed superior clinical outcomes compared with conventional treatment.